Guidelines for assessing single borehole yields in secondary aquifers - Murray, Eric Charles (Rhodes University, Faculty of Science, Department of Geography, 1997)
The motivation for this research project arose from the realisation that many South African rural water supply schemes fail due to the over abstraction of groundwater from single boreholes. The main reason for this mis-management of groundwater is a result of inappropriate borehole yield recommendation methods. This research project set out to review existing borehole yield assessment methods and establish new methods which take the shortcomings of existing methods into account. The study is concerned with borehole yield assessment methods applicable to secondary aquifers, since these aquifers are by far the most common in South Africa. The yield assessment methods have been grouped into those that are based on aquifer yield analyses, and on the analysis of single borehole test pump data. In order to assess which methods give suitable yield recommendations, it was necessary to compare the yields obtained using the various methods, with established yields from production boreholes. The focus of the aquifer yield component of the study, was to develop a method for estimating the proportion of recharge that can be abstracted from a single borehole located in a relatively small aquifer. The method was developed by computer simulations of aquifers with different hydraulic properties, and by establishing a formula which describes the relationship between recharge and the abstractable proportion of recharge. Under specific hydrogeological conditions, the recharge based method proved to be reliable in relation to established yields from production boreholes. Of the borehole yield assessment methods based on the analysis of test pump data, none of the existing methods proved to be reliable. However, the yields obtained using the two newly developed methods compared favourably to the established yield of existing production boreholes. Both of these methods are based on the application of the Cooper-Jacob approximation of the Theis equation. This study reviews existing methods and presents newly developed methods for recommending borehole abstraction rates in secondary aquifers. While existing borehole yield assessment methods were found to be unreliable, some of the newly developed methods, if correctly applied, give acceptable yield recommendations.
Keywords: Aquifers -- Measurement